Hypothermia during microsurgical head and neck reconstruction and incidence of venous thromboembolism - Saadoun, Rakan; Guerrero, David T.; Bengur, Fuat Baris; Moroni, Elizabeth A.; Surucu, Yusuf; Smith, Roy E.; Esper, Stephen A.; Whitehurst, Steven L.; Artman, Jamie; Veit, Johannes Adrian; Kubik, Mark; Sridharan, Shaum; et al. (JAMA otolaryngology - head & neck surgery, 2024)
Venous thromboembolism (VTE) is a severe complication after microsurgical free tissue transfer (FTT) to the head and neck. Hypothermia during surgery is a modifiable risk factor, and avoiding it may reduce the postoperative VTE rate.To assess the association between hypothermia (temperature <36 °C) and postoperative VTE and free flap pedicle thrombosis rates after head and neck reconstruction with FTT.This retrospective cohort study in a tertiary academic referral center used prospective and retrospective database and medical record data collected for patients who underwent head and neck reconstruction with FTT between January 1, 2012, and August 31, 2023. Temperature over time was classified as normothermia (temperature ≥36 °C), hypothermia (<36 °C) for more than 30 minutes and less than 120 minutes, and hypothermia for 120 minutes or more.Venous thromboembolism.The study outcomes were VTE events and thrombosis of the free flap pedicle that required revision surgery. Univariable and multivariable regressions were used to test the association between the outcomes and clinical factors.A total of 1078 patients (mean [SD] age, 61.3 [12.6] years; 724 males [67.2%]; mean [SD] Caprini score, 6.4 [2.1]) were included. The VTE and pedicle thrombosis rates were 3.2% (35 patients) and 2.2% (24 patients), respectively. In a multivariable model controlled for Caprini score and chemoprophylaxis, VTE was associated with hypothermia of more than 30 minutes and less than 120 minutes (odds ratio [OR], 3.82; 95% CI, 0.99-14.07) and hypothermia of 120 minutes or longer (OR, 3.55; 95% CI, 1.05-11.95). Free flap pedicle thrombosis was not associated with hypothermia (OR, 0.61; 95% CI, 0.26-1.43).These findings suggest that preventing hypothermia during microsurgical FTT to the head and neck may decrease the postoperative rate of VTE. Future studies should explore the optimal intraoperative body temperature range that may prevent the development of VTE without compromising patient safety.
Gesehen am 29.04.2025